SOCIEDADE CIVIL E BASES DA EDUCAÇÃO: novo tempo para manifestos ou manifestos para novo tempo? - Urânia Flores da Cruz Freitas (Universidade Federal do Maranhão, 2019)
This article evidences historically the inequalities and the actions of the civil society inscribed in the Brazilian education manifestos. Based on a theoretical study, bibliographical and documentary research, it aims to analyze how this Actor-Network understood and reacted to the Brazilian development process and its relations in the field of education. It points out that the writings served as a contribution to the understanding of the conjuncture of each historical time because they bring the scenario in which they entered, the struggles and the achievements. It reveals how these actors perceived or not the basis that structured education in Brazil, as well as the importance of the political instruments of public action. It also emphasizes how the historical movement of the basis of educational and social structure can contribute on reflect upon the current political time.